1989
DOI: 10.1002/bjs.1800760409
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless large bowel anastomosis: European experience with the biofragmentable anastomosis ring

Abstract: Sutureless colonic anastomosis using a biofragmentable anastomosis ring (BAR) has been evaluated in a prospective randomized comparison with sutures and staples for elective colorectal surgery. One hundred and one patients underwent BAR anastomosis, 85 a sutured anastomosis, and 16 a stapled anastomosis. There were two anastomotic leaks in the patients undergoing BAR anastomosis, seven in patients having a sutured anastomosis, and one in a patient who had a stapled anastomosis. Wound infection occurred in ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 4 publications
2
46
0
5
Order By: Relevance
“…141 Today the biofragmentable anastomotic ring, made of absorbable polyglycolic acid, is used most often. Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%
“…141 Today the biofragmentable anastomotic ring, made of absorbable polyglycolic acid, is used most often. Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%
“…Findings from other clinical studies in which a compressive anastomotic device was used for lower gastrointestinal surgery showed advantages in terms of overall operation time, postoperative complications, and recovery of bowel function, as well as anastomotic time [16,22,23]. Jejunojejunostomy in total gastrectomy for the treatment of gastric cancer is basically a small part of the entire operation.…”
Section: Discussionmentioning
confidence: 99%
“…A semelhança no resultado das anastomoses do intestino grosso realizadas com anel biofragmentável, com grampeador e com sutura manual tem sido evidenciada em estudos experimentais 11,13,37 e clínicos 13,[38][39][40] . Existem algumas vantagens do anel biofragmentável em relação aos outros métodos, como ausên-cia de corpos estranhos nas anastomoses, possibilidade de utilização em qualquer ponto do intestino dentro da cavidade abdominal e representação de técnica padronizada 40 .…”
Section: Discussionunclassified